1997
DOI: 10.1038/bjc.1997.435
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor type 2 in breast cancer

Abstract: Summary The serine protease urokinase plasminogen activator (uPA) is causally involved in cancer invasion and metastasis. Activity of this protease in vivo is controlled principally by two inhibitors, one of which is plasminogen activator inhibitor type 2 (PAI-2). In this study, we show that PAI-2 levels were significantly higher in primary breast carcinomas (n = 152) than benign breast tumours (n = 18). In the primary cancers, PAI-2 levels correlated weakly but significantly with those of uPA and PAI-1, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 19 publications
5
36
1
1
Order By: Relevance
“…Furthermore, in the u-PA-positive cases, the survival rate of patients with negative mRNA expression of PAI-2 was significantly worse than that of patients with positive mRNA expression of PAI-2 in lung cancers. These results support the findings that depressed PAI-2 antigen detected by the immunoenzymic method is correlated with a shortened disease-free survival in breast cancer (Foekens et al, 1995;Duggan et al, 1997) and that the occurrence of lymph node metastasis follows diminished expression of PAI-2 in breast cancer (Ishikawa et al, 1996), non-small-cell lung cancer (Nagayama et al, 1994) and colon cancer (Naitoh et al, 1995). Our previous and present findings and the reports of others suggest that PAI-2 is a more important inhibitor of u-PA activity than PAI-1.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, in the u-PA-positive cases, the survival rate of patients with negative mRNA expression of PAI-2 was significantly worse than that of patients with positive mRNA expression of PAI-2 in lung cancers. These results support the findings that depressed PAI-2 antigen detected by the immunoenzymic method is correlated with a shortened disease-free survival in breast cancer (Foekens et al, 1995;Duggan et al, 1997) and that the occurrence of lymph node metastasis follows diminished expression of PAI-2 in breast cancer (Ishikawa et al, 1996), non-small-cell lung cancer (Nagayama et al, 1994) and colon cancer (Naitoh et al, 1995). Our previous and present findings and the reports of others suggest that PAI-2 is a more important inhibitor of u-PA activity than PAI-1.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, several studies in breast cancer have indicated that high tumor tissue concentrations of PAI-2 are associated with better prognosis. 15,20,21,37 Findings in patients with small cell lung cancer seem to agree with those in breast cancer, since low tumor content of PAI-2 correlated with advanced stage of the disease. 38 PAI-2 is abundant in placental tissue and is also known to be produced by activated human monocytes and certain malignant cells.…”
Section: Discussionsupporting
confidence: 63%
“…However, high pAI-2 levels are associated with aggressive disease in colorectal cancer (Verspaget et al, 1995) and in bladder cancer cell lines, pAI-2 expression correlates with tumour stage and with a low overall survival (Champelovier et al, 2002). Paradoxically, in breast cancer, high levels of pAI-2 have been reported to be a favourable prognostic marker (Duggan et al, 1997) and in vitro pAI-2 expression can inhibit cancer cell invasion and metastasis (Mueller et al, 1995). In this study, pAI-2 was over-represented in 14/35 NSCLCs compared to corresponding normal lung.…”
Section: Discussionmentioning
confidence: 99%